Polygon method: A systematic margin assessment for breast conservation. (7th May 2019) - Ichihara, Shu; Moritani, Suzuko; Nishimura, Rieko; Oiwa, Mikinao; Morita, Takako; Hayashi, Takako; Kato, Aya; Endo, Tokiko; Kada, Akiko; Ito, Noriko; Kuroishi, Tetsuo; Sato, Yasuyuki
Abstract: Background: Radiation therapy (RT) for women with ductal carcinoma in situ (DCIS) undergoing breast‐conserving surgery (BCS) may be overtreatment for some, especially for those in which DCIS is eradicated, and ipsilateral breast tumor recurrence (IBTR) risk approaches the contralateral breast cancer (CBC) level. The aim of this study was to clarify whether the polygon method, a new systematic method of en face (tangential, shaved) margin assessment, can identify a subset of DCIS that can be safely treated by BCS alone. Methods: A key tool of the polygon method is an adjustable mold that prevents the "pancake phenomenon" (flattening) of breast tissue after surgical removal so that the specimen is fixed in the shape of a polygonal prism. This preanalytical procedure enables us to command a panoramic view of entire en face margins 3‐5‐mm deep from the real peripheral cut surfaces. Competing risk analysis was used to quantify rates of IBTR and CBC and to evaluate risk factors. Results: From 2000 to 2013, we identified 146 DCIS patients undergoing BCS with a contralateral breast at risk. In 100 DCIS patients whose margin was negative by the polygon method, 5 IBTR (3 DCIS and 2 invasive ductal carcinoma [IDC]) and 10 CBC (6 DCIS and 4 IDC) cases were identified during a median follow‐up of 7.6 years (range, 0.9‐17.4). Five‐ and 10‐year cumulative incidence rates were 3.0% and 5.3% for IBTR, and 7.1% and 13.3% for CBC, respectively. Thus, patients with a negative margin consistently showed at least twofold lower IBTR than CBC despite omission of RT. Conclusions: Japanese women classified with a negative margin by the polygon method show a very low risk of IBTR and account for approximately half of CBC cases. In this subset of DCIS patients, additional RT is not beneficial. Abstract : In order to check the entire interphase between the resected and the preserved breast tissue, a systematic margin assessment (the polygon method) has been developed and a retrospective cohort study to reveal the impact of this method on ipsilateral breast tumor recurrence (IBTR) in Japanese women (n = 146) was performed. On competing risk regression, patients with a negative margin consistently showed at least twofold lower IBTR than contralateral breast cancer, despite radiation being omitted.